2017
DOI: 10.1016/j.ebiom.2017.07.010
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Mediating Immunopathological Lesions: A Potential Treatment Option for Severe Influenza A Diseases

Abstract: Severe influenza diseases with high mortality have been frequently reported, especially in those patients infected with avian influenza A (H5N1, H7N9 or H10N8) or during a pandemic. Respiratory distress, which is attributed to alveolar damage associated with immunopathological lesions, is the most common cause of death. There is a wealth of information on pathogenesis or treatment options. In this study, we showed that high levels of C-reactive protein (CRP) were induced and correlated with complement activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 59 publications
5
28
0
Order By: Relevance
“…Previous studies suggested that excessive immune response played an important role on pathogenesis of severe influenza or SARS [24]. And IL-6 and CRP may link to the excessive immune response [25,26]. In this study, our results also showed abnormally increased CRP and IL-6 in most of both NCOVID-19 and NON-NCOVID-19 patients.…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies suggested that excessive immune response played an important role on pathogenesis of severe influenza or SARS [24]. And IL-6 and CRP may link to the excessive immune response [25,26]. In this study, our results also showed abnormally increased CRP and IL-6 in most of both NCOVID-19 and NON-NCOVID-19 patients.…”
Section: Discussionsupporting
confidence: 73%
“…In animal and cell culture models, among other cytokines, over-synthesis of interleukins (such as IL-1β and IL-6) and TNF-α were shown to play a major role in the development of a wide range of severe disease outcomes [reviewed in 8, 11]. Furthermore, cytokine storm has been implicated previously both in severe H5N1 and H7N9 influenza [26, 27] where excessive immune activation, particularly the complement activation mediated by CRP, was reported [27]. …”
Section: Discussionmentioning
confidence: 99%
“…CRP is an acute phase reactant activated by cytokines to trigger the complement component of the immune system [10, 11, 27]. Previous studies in influenza A have shown that overactivation of the complement cascade contributes to the cytokine storm and can play a role in the pathogenesis of, rather than protection against, influenza [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…We also find that the peak CRP level may be considered a particularly important factor when evaluating the probability associated with survival in H7N9 cases. According to a study conducted by Gao and colleagues, 31 CRP is involved in the deterioration observed in severe influenza infection and may be a candidate molecule for immunotherapy treatment. A previous study 31 indicated that CRP treatment can improve the prognosis of patients with H7N9 VI.…”
Section: Discussionmentioning
confidence: 99%